USES AND ABUSES OF APOCALYPTICISM IN SOUTH ASIA: A CREATIVE HUMAN DEVICE - Forsthoefel, Tom (Journal of Dharma, 2001)
If anything is clear from all the hype of Y2K and its subsequent bubble-burst into pedestrian normalcy, it should be that time in an arbitrary human construction, artfully and not-so-artfully used, as a part of a rhetoric of persuasion, to generate meaning, purpose, and the assuredness Of one’s convictions. The apparent arbitrariness Of time is certainly seen in the divergent calendars of various religious traditions, many of which organize time around foundational or seminal events, such as the Buddha’s Enlightenment, the Exodus, the Resurrection of Jesus. Religious festivals accompanying these events such as these are clearly rites of renewal, drawing time into the orbit of the sacred and imposing a spiritual order onto the world of ordinary history and change. But the arbitrariness of these diverse temporal systems is also revealed in the occasional bemusement of some non-Christian thinkers with the Western hype, fueled in part by religious rhetoric of the end times, with the turn of the millennium. Vasudha Narayanan, for example, nicely captures this sensibility in the title of her recent article on Hindu conceptualizations of time ’Y51K and Conuting."